2016
DOI: 10.14814/phy2.12893
|View full text |Cite
|
Sign up to set email alerts
|

The response of muscle protein synthesis following whole‐body resistance exercise is greater following 40 g than 20 g of ingested whey protein

Abstract: The currently accepted amount of protein required to achieve maximal stimulation of myofibrillar protein synthesis (MPS) following resistance exercise is 20–25 g. However, the influence of lean body mass (LBM) on the response of MPS to protein ingestion is unclear. Our aim was to assess the influence of LBM, both total and the amount activated during exercise, on the maximal response of MPS to ingestion of 20 or 40 g of whey protein following a bout of whole‐body resistance exercise. Resistance‐trained males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
140
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 29 publications
(112 reference statements)
7
140
0
3
Order By: Relevance
“…Nevertheless, the lighter participants did to some extent reach higher leucine levels with native whey than heavier participants. This observation is in line with a recent study finding no differences in the time dependent changes in blood leucine concentrations after intake of 20 g of whey protein in a group with low lean mass (<65 kg) to a group with high lean mass (>70 kg) [29]. Combined these findings might suggest that a certain amount of leucine is needed on order for leucine kinetics to be affected by body mass.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the lighter participants did to some extent reach higher leucine levels with native whey than heavier participants. This observation is in line with a recent study finding no differences in the time dependent changes in blood leucine concentrations after intake of 20 g of whey protein in a group with low lean mass (<65 kg) to a group with high lean mass (>70 kg) [29]. Combined these findings might suggest that a certain amount of leucine is needed on order for leucine kinetics to be affected by body mass.…”
Section: Discussionsupporting
confidence: 92%
“…Ingestion of 20 g egg or whey protein has been shown sufficient to maximize muscle protein synthesis rates during recovery from lower-body resistance-type exercise in young males [4,5]. More recent evidence indicates that this dose-response relationship may depend on the amount of muscle tissue that was recruited during exercise, with the ingestion of 40 g protein further increasing muscle protein synthesis rates during recovery from whole-body resistance-type exercise [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the amount and distribution of protein throughout the day is associated with positive changes in body composition (Houston et al, 2008;Loenneke et al, 2010Loenneke et al, , 2016Adechian et al, 2012), bone health (Loenneke et al, 2010) and muscle function (Deutz et al, 2014). It has been demonstrated that there is a dose-response in muscle protein synthesis (MPS) with regard to protein ingestion , with the synthetic response plateauing around 20-40 g depending on the age group (Cuthbertson et al, 2005), amount of exercise (Macnaughton et al, 2016) and quality of protein Norton et al, 2009;Yang et al, 2012). Interestingly, the literature with regard to protein timing has primarily focused on increased MPS in response to an exercise stimulus (Burd et al, 2009).…”
Section: Introductionmentioning
confidence: 99%